Exploring the cytotoxicity on human lung cancer cells and DNA binding stratagem of camptothecin functionalised silver nanoparticles through multi-spectroscopic, and calorimetric approach - Aparna Raj; Riju K. Thomas; L. Vidya; V. M. Aparna; S. Neelima; C. Sudarsanakumar (Scientific Reports, 2023)
Abstract The influence of nanoparticles inside the human body and their interactions with biological macromolecules need to be explored/studied prior to specific applications. The objective of this study is to find the potential of camptothecin functionalised silver nanoparticles (CMT-AgNPs) in biomedical applications. This article primarily investigates the binding stratagem of CMT-AgNPs with calf thymus DNA (ctDNA) through a series of spectroscopic and calorimetric methods and then analyses the anticancer activity and cytotoxicity of CMT-AgNPs. The nanoparticles were synthesized using a simple one pot method and characterized using UV–Visible, fourier transform infrared (FTIR) spectroscopy, X-ray diffraction and high-resolution transmission electron microscopy (HRTEM). The average size of CMT-AgNPs is 10 ± 2 nm. A group of experimental techniques such as UV–Visible spectrophotometry, fluorescence dye displacement assay, circular dichroism (CD) and viscosity analysis unravelled the typical groove binding mode of CMT-AgNPs with ctDNA. The CD measurement evidenced the minor conformational alterations of double helical structure of ctDNA in the presence of CMT-AgNPs. The information deduced from the isothermal titration calorimetry (ITC) experiment is that the binding was exothermic and spontaneous in nature. Moreover, all the thermodynamic binding parameters were extracted from the ITC data. The binding constants obtained from UV absorption experiments, fluorescence dye displacement studies and ITC were consistently in the order of 104 Mol−1. All these results validated the formation of CMT-AgNPs–ctDNA complex and the results unambiguously confirm the typical groove binding mode of CMT-AgNPs. An exhaustive in vitro MTT assay by CMT-AgNPs and CMT against A549, HT29, HeLa and L929 cell lines revealed the capability of CMT-AgNPs as a potential anticancer agent.